A novel HLA‐DRB1 allele, HLA‐DRB1*12:48. (22nd February 2016) - Zhu, X.; Yang, T.; Tan, R.; Su, P.; Gao, H.
Abstract : HLA‐DRB1*12:48 differs from DRB1*12:09, by a single synonymous nucleotide at position 266.